Oral papillary squamous cell carcinoma (OPSCC): a rare presentation in the palate - Karthik K.P; Balamurugan R.; Sahana Pushpa T. (EDP Sciences, 2020)
Introduction: Oral papillary squamous cell carcinoma (OPSCC) is a rare variant of squamous cell carcinoma with an unusual presentation in the palate. Observation: This case report presents a 68 year old male who reported with pain in the roof of the jaw for the past one month. The patient gave a history of a small ulcer over the right palatal region since a year which gradually increased in size. History also revealed that he was a tobacco chewer for around five years and had quit the habit one year back. Clinically, a proliferative growth in the right palatal region was apparent. The growth was firm in consistency and had well-defined borders that crossed the midline of palate. Based on the noticeable clinical signs, the case was provisionally diagnosed as verrucous carcinoma. Histopathology report of the incisional biopsy confirmed the case to be non-invasive oral papillary squamous cell carcinoma. Commentary: OPSCC displays either a papillary variant or exophytic pattern. It has a better prognosis than squamous cell carcinoma of similar clinical stage but is worse than verrucous carcinoma. Conclusion: Since OPSCC may mimic other benign conditions of oral cavity, evaluation of clinical parameters that are associated with the risk of carcinoma is mandatory. This article highlights the significance of histopathological examination that aids the clinician to arrive at a diagnosis for any suspicious papillary lesions.